2012
DOI: 10.1111/j.1748-720x.2012.00683.x
|View full text |Cite
|
Sign up to set email alerts
|

Conflicts of Interest, Institutional Corruption, and Pharma: An Agenda for Reform

Abstract: When physicians' conflicts of interest arise from ties with drug firms, we should shift our focus to the pharmaceutical industry and improper dependencies that cause institutional corruption. This article analyzes eight forms of improper dependencies on pharma and proposes reforms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 31 publications
0
28
0
9
Order By: Relevance
“…16 Such conflicts of interest are "inevitable and pervasive in our health care system," 17 and, as illustrated by passage of the Sunshine Act, these conflicts are "as much matters of public policy and management as individual choices or social norms." 18 When confronted with the pervasiveness of financial conflicts of interest, most physicians -reflecting the psychological research showing that each of us is prone to have an optimistic, often unconscious and unintentional, bias about ourselves -will deny that they are influenced by financial transactions with industry. 19 An overwhelmingly convincing body of research, however, suggests otherwise.…”
Section: Introductionmentioning
confidence: 99%
“…16 Such conflicts of interest are "inevitable and pervasive in our health care system," 17 and, as illustrated by passage of the Sunshine Act, these conflicts are "as much matters of public policy and management as individual choices or social norms." 18 When confronted with the pervasiveness of financial conflicts of interest, most physicians -reflecting the psychological research showing that each of us is prone to have an optimistic, often unconscious and unintentional, bias about ourselves -will deny that they are influenced by financial transactions with industry. 19 An overwhelmingly convincing body of research, however, suggests otherwise.…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that these practices are by no means restricted to operations in emerging markets (Oldani, 2004;Rodwin, 2012;European Commission, 2013). One study conducted in 2007 showed that 83% of US physicians received gifts from the industry, while 28% received payments for services such as honoraria for speaking at conferences and consulting fees (Campbell, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These problems are exacerbated by the medical community's dependence on pharmaceutical corporations for funding. 30 Most reform plans to resolve these and other problems involve new legislation, or a change in legal enforcement and administration so that tradeoffs between profit maximization and public health are not as stark. Proposals such as economist Dean Baker's plan for public funding of clinical trials 31 do not advance as legislation, largely because of industry funding of electoral campaigns and lobbying.…”
Section: What Could Have Been? the Legislative Victories For The Pharmentioning
confidence: 99%